Metacognition and action: a new pathway to understanding social and cognitive aspects of expertise in sport - MacIntyre, Tadhg E.; Igou, Eric R.; Campbell, Mark J.; Moran, Aidan P.; Matthews, James (Frontiers in Psychology, 2014)
For over a century, psychologists have investigated the mental processes of expert performers - people who display exceptional knowledge and/or skills in specific fields of human achievement. Since the 1960s, expertise researchers have made considerable progress in understanding the cognitive and neural mechanisms that underlie such exceptional performance. Whereas the first modern studies of expertise were conducted in relatively formal knowledge domains such as chess, more recent investigations have explored elite performance in dynamic perceptual-motor activities such as sport. Unfortunately, although these studies have led to the identification of certain domain-free generalizations about expert-novice differences, they shed little light on an important issue: namely, experts’ metacognitive activities or their insights into, and regulation of, their own mental processes. In an effort to rectify this oversight, the present paper argues that metacognitive processes and inferences play an important if neglected role in expertise. In particular, we suggest that metacognition (including such processes as ‘meta-attention’, ‘meta-imagery’ and ‘meta-memory’, as well as social aspects of this construct) provides a window on the genesis of expert performance. Following a critique of the standard empirical approach to expertise, we explore some research on ‘metacognition’ and ‘metacognitive inference’ among experts in sport. After that, we provide a brief evaluation of the relationship between psychological skills training and metacognition and comment on the measurement of metacognitive processes. Finally, we summarize our conclusions and outline some potentially new directions for research on metacognition in action.